XGASS: passive discs do not host unexpectedly large reservoirs of cold atomic hydrogen. (19th February 2020) - Cortese, L; Catinella, B; Cook, R H W; Janowiecki, S
ABSTRACT: We use the extended GALEX Arecibo SDSS Survey (xGASS) to quantify the relationship between atomic hydrogen (H i ) reservoir and current star formation rate (SFR) for central disc galaxies. This is primarily motivated by recent claims for the existence, in this sample, of a large population of passive discs harbouring H i reservoirs as large as those observed in main-sequence galaxies. Across the stellar mass range 10 9 < M * /M⊙ < 10 11, we practically find no passive (≳2σ below the star forming main sequence) disc galaxies with H i reservoirs comparable to those typical of star-forming systems. Even including H i non-detections at their upper limits, passive discs typically have ≥0.5 dex less H i than their active counterparts. We show that previous claims are due to the use of aperture-corrected SFR estimates from the MPA/JHU SDSS DR7 catalogue, which do not provide a fair representation of the global SFR of H i -rich galaxies with extended star-forming discs. Our findings confirm that the bulk of the passive disc population in the local Universe is H i -poor. These also imply that the reduction of star formation, even in central disc galaxies, has to be accompanied by a reduction in their H i reservoir.